Characterization of Benitaka Grape Pomace (Vitis vinifera L.): An Analysis of Its Properties for Future Biorefinery Applications - Luiz Eduardo Nochi Castro; Tiago Linhares Cruz Tabosa Barroso; Vanessa Cosme Ferreira; Tânia Forster Carneiro (Waste)
This study investigates the properties of Benitaka grape pomace (Vitis vinifera L.), a byproduct of the wine industry, focusing on its potential for applications in the circular economy and biorefinery processes. The analysis covers a range of physical, chemical, and structural characteristics, including the composition of proteins, moisture, lipids, ash, sugars, fiber fractions (such as neutral-detergent fiber, cellulose, lignin, and hemicellulose), pH, acidity, gross energy, as well as bioactive compounds such as total phenolics, flavonoids, anthocyanins, and antioxidant capacity. Advanced characterization techniques, such as nitrogen adsorption/desorption isotherms, Fourier-transform infrared spectroscopy, differential scanning calorimetry, scanning electron microscopy, and high-performance liquid chromatography coupled with mass spectrometry, were employed. The results revealed an acidic pH of 4.05 and a titratable acidity of 1.25 g of tartaric acid per 100 g. The gross energy was 3764 kcal kg−1, indicating high energy capacity, similar to wood chips. The pomace exhibited high hygroscopicity (31 to 50 g of moisture per 100 g), high levels of fiber, cellulose, and lignin, as well as bioactive compounds with significant values of total phenolics (5956.56 mg GAE 100 g−1), flavonoids (1958.33 mg CAT 100 g−1), and anthocyanins (66.92 mg C3G 100 g−1). Antioxidant analysis showed promising results, with DPPH and FRAP values of 20.12 and 16.85 μmol TEAC g−1 of extract, respectively. This study not only validates existing data but also provides new insights into the composition of hemicellulose and lignocellulosic phase transitions, highlighting grape pomace as a promising resource for sustainability in industry and biorefinery processes.